1986
DOI: 10.1002/ana.410190103
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic cerebral vasculopathy associated with herpes zoster

Abstract: We describe the clinical, radiographic, and pathological findings in 3 patients with large-vessel cerebral vasculopathy following herpes zoster. Two of the patients were studied at postmortem examination, and a brain biopsy was performed in the third. Each of the 3 patients suffered thrombotic occlusions of large vessels without notable inflammatory or granulomatous changes following trigeminal or segmental herpes zoster infection. In the 2 autopsied patients, varicella-zoster virus (VZV) antigens were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(68 citation statements)
references
References 22 publications
3
62
0
3
Order By: Relevance
“…Eidelberg et al 26 described 2 fatal cases of VZV vasculopathy of 3 and 10 months duration, respectively. In both cases, VZV antigen was found in the media of MCA without inflammation.…”
Section: Figure 3 T-cell Subsets In Varicella-zoster Virus (Vzv) Vascmentioning
confidence: 99%
“…Eidelberg et al 26 described 2 fatal cases of VZV vasculopathy of 3 and 10 months duration, respectively. In both cases, VZV antigen was found in the media of MCA without inflammation.…”
Section: Figure 3 T-cell Subsets In Varicella-zoster Virus (Vzv) Vascmentioning
confidence: 99%
“…Some infections, such as cytomegalovirus [9,27,28], herpes zoster [9,[29][30][31] and tuberculosis [9,32,33], are known to produce vasculitis and infarction in the CNS. Gillams et al [20] found strong evidence of opportunistic infection as a cause of cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…12 Neuropathologic evaluation may demonstrate initial involvement of the proximal anterior or middle cerebral arteries with widespread infarction and diffuse thromboses of the leptomeningeal arteries. [12][13][14] We deferred cerebral angiography for our patient based on her critical status at time of admission. The magnetic resonance angiography demonstrated segmental narrowing of the proximal middle and anterior cerebral arteries in the M1 and A1 segments bilaterally.…”
Section: Discussionmentioning
confidence: 99%